3D Printed Transmission Type Phase Shifter Based on Tunable Liquid Crystals - Pietschmann, Simon; Bilchenko, F.; Maune, H.; Shi, Jing; Bachbauer, Felix; Gold, Gerald (2024 54th European Microwave Conference, EuMC 2024, 2024)
This work presents an additively manufactured transmission phase shifter operating at 60 - 65 GHz based on the relative permittivity change obtained from rotating anisotropic liquid crystals (LC) by an external field. A slotted waveguide structure is filled with a printed inlay that provides the cavity for holding the LC material. To reduce the reflection at the transition from the empty to the filled waveguide, various types of inlays are being investigated.
CRIS-Team Scopus Importer:2024-12-13
Keywords: additive manufacturing; liquid crystal; phase shifter; reconfigurable components; slotted waveguide